Pedagogical Pathways on Entrepreneur and Religious Culture to Madrasah Graduate Quality - As'ari As'ari; Juhji Juhji; Apud Apud; Nur Aida Tahirulla Samson (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Teacher pedagogical competence in practice constitutes a key to the quality of madrasah graduates. Practicing needs to be integrated into the religious culture and the supported madrasah environment, as well as entrepreneurial leadership. The research objective is to describe quality teaching practices integrated with entrepreneurial leadership and religious cultures that lead to higher graduate quality. This research employed a mixed-methods approach. This study involved a 349-teacher proportional stratified random sample. Participatory observation, in-depth interviews, and documentation are also employed to adopt a qualitative approach in describing each variable. Quantitative data were analyzed using path analysis to determine the contribution of each coefficient to the causal relationships among variables. Pedagogical competence exhibits the strongest and most significant influence on graduate quality, as indicated by its t-value. This research indicates that teacher pedagogical competences are integrated into the religious culture program as the basis of madrasah principles and polices. Madrasahs need to focus on teacher pedagogical skills, Islamic pedagogy, and integration of religious values into subject teaching. Principals must be visionary on curriculum integration, such as designing a holistic curriculum that blends general education with Islamic teachings, using local wisdom and religious culture as contextual learning tools, and promoting interdisciplinary approaches where Islamic values are embedded across subjects. Ultimately, transformative and visionary leadership in madrasahs is necessary to inspire religious commitment and academic rigor, facilitate innovation, and maintain the quality of madrasah graduates.